2023
DOI: 10.1088/2053-1591/acf6f3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the physical properties and filtration efficiency of PVDF/PAN nanofiber membranes by using dry milk protein

Wissam Mohammed Mustfa,
Salih Abbas Habeeb

Abstract: In engineering applications, especially ultrafiltration (UF) applications, it is very important to use polyacrylonitrile (PAN) and poly (vinylidene fluoride) (PVDF) nanofiber membranes. In this study, membrane nanofibers made of pure PAN, PVDF: PAN blends, and pure PVDF (M1, M2, M3, M4, M5, and M6), were produced by the electrospinning technique with different contents of PVDF in each blend. The prepared membranes were characterized by field emission scanning electron microscopy (FE-SEM), atomic force microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The uniform distribution of lead nanoparticles enhances mechanical properties and contributes to the enhanced resistance of rubber models to gamma-ray shielding properties. The current study showed that increasing the concentration of lead nanoparticles increases the cutting distance and the nal force [32][33][34].…”
Section: Characterizationsmentioning
confidence: 55%
“…The uniform distribution of lead nanoparticles enhances mechanical properties and contributes to the enhanced resistance of rubber models to gamma-ray shielding properties. The current study showed that increasing the concentration of lead nanoparticles increases the cutting distance and the nal force [32][33][34].…”
Section: Characterizationsmentioning
confidence: 55%
“…There were asymmetric stretching vibration bands at 836 and 1273 cm – 1 , and a bending vibration band associated with −CF 2 was identified at 475 cm – 1 . These peaks were identical to the chemical structure of PVDF. In the spectra of PVDF/Fe 3 O 4 and PVDF/Fe 3 O 4 @pDA NFMs, the characteristic peak at 562 cm – 1 was assigned to Fe–O stretching in Fe 3 O 4 NPs. , Moreover, in the PVDF/Fe 3 O 4 @pDA spectrum, −NH bending vibration was detected near 1597 cm – 1 due to a large amount of −NH in pDA. , In the PVDF/Fe 3 O 4 @pDA@Ag spectrum, due to the complete coverage of the fiber surface by the Ag layer, only the Ag–O characteristic peak at 533 cm – 1 was detected …”
Section: Resultsmentioning
confidence: 73%
“…The percentage of increment in the pore volume was 263.78 % after adding 3 mM SDBS to the PUL-g-AM /AA; the results of pore volume (nm 3 ) and porosity % of SAPs are shown in Table 2. The pore volume of the hydrogel increased with SDBS compared to the pore volume of the hydrogel that did not contain SDBS [41].…”
Section: Samples Composition Of Sapsmentioning
confidence: 91%